ВОПРОС ОБ АНТРОПОЦЕНТРИЧЕСКОМ ЛЕКСИКОГРАФИРОВАНИИ СИНОНИМОВ РУССКОГО СЛОВА В ДВУЯЗЫЧНОМ СЛОВАРЕ (Journal of Oriental Studies, 2016)
It is recognized that the synonyms of the Russianlanguage capabilities are great. For the expression of aconcept can be used not one word to express the range andvariety of shades of meaning. In this case the inability tochoose words and designs that express the desired value,leads to a semantic error. Information about thecharacteristics of synonyms, the difference between them isvery relevant to any speaker in that language, rather than aninterpreter, who must learn the differences betweensynonyms for the correct, adequate expression of theconcept.In this paper we examine how the Russian synonyms arepresented in a Russian-Arabic dictionary and will bepresented the mechanism of the lexicographic description ofthe studied units, which would take into account all aspectsof synonyms.